Kelayakan Bisnis dan Pemasaran Tahu Jojoh di Kecamatan Karangpawitan, Kabupaten Garut - Vela Rostwentivaivi; Atia Fizriani (Universitas Muhammadiyah Parepare)
Tofu is a processed food from soy that has a high protein content. Tofu consumption of Indonesian people is higher than tempe consumption, which is 1,425 ounces per week. Tofu processing in Garut Regency is mostly on a household scale with limited and simple equipment. Partners are Jojoh tofu craftsmen, where jojoh tofu marketing is still relatively limited, making tofu craftsmen only market their products around production areas and traditional markets. The purpose of the Community Partnership Program is to analyze the business feasibility and marketing of Jojoh's tofu and financial literacy, specifically marketing and financial aspects. Mix marketing strategy is one of the strategies that can be used. For financial literacy is to understand the financial aspects consisting of investment costs, fixed costs, and variable business costs. The results of the joint assistance show that Jojoh's tofu business is worth developing. This can be seen from several feasibility indicators, such as NPV Rp 97,126,405.33; IRR 85 percent; Net B/C 2.73; and Gross B/C 1.09.